Detection of Parvovirus B19 Infection in Thalasemic Patients in Tikrit City, Serological Study (Medico Legal Update, 2020)
Background:-ParvovirusB19, a member of the genus Erythrovirus virus of the Parvoviridae family, causes several clinical diseases including infectious erythematosus, joints, fetalis hydrops or chronic hemolytic anemia like thalassemia syndrome, transient aplastic crises. B19 can be transmitted through respiratory secretions, blood products, and blood transfusions.Objective: To identify the seroprevalence of Human Parvovirus B19 virus in Patients with thalassemia major in Tikrit city.Material and method:- This lessons is a cross-sectional case control study that included 130 Patients infection with beta thalassemia attendance the Tikrit Military Hospital Department of Blood Diseases Unit as of 1/7 /2018 to 1/12/2018 major age ranging from 1-60 years and 50 healthy patients as control grouping. Blood sample were obtain for determination of specific antibodies IgG and IgM for HPV-B19 by enzyme linked immunoassay (ELISA).Results:- HPV B19 IgM antibodies were detected in 15 of 130 thalassemic patient(11.5%),and not detected in any patient of control group, P value ( 0.02).While anti-HPV B19 IgG antibodies were detected in 50 of 130 of thalassemic patient (38.5 %)and 2(4%) of 50 in control group(5%), P value(0.003).. the range age of the thalassemia patient was (2 –58 years) and B19 infection was highest in the 20-to-40 year range. And the result show the highest percentage to infected to virus during the blood transfusions once a month per month was 30(100%) anti-B19IgG and 8(26.7%) anti-B19IgM.Conclusion:-In this study, acute B19 infections were detect in patients with beta thalassemia major. showing of such high-risk groups can significantly reduce the incidence and prevalence of B19 infection; thus, screening is required for epidemiologic surveillance and disease-prevention measures.